The examination questionnaires of Boncho Bochev as a key to his conducting method - Georgieva, Iva (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
Children Choir â€žBodra Smyanaâ€œ under the direction of Boncho Bochev in the period from the 1940s to the 1970s became a choir with unparalleled artistic accomplishments. The conductor built a refined mechanism for admission of choristers that reflected his vision of choral quality. This report looks at the qualities and skills of the candidates and the way of their improvement during the rehearsal process. Because of the great interest, â€žBodra Smyanaâ€â€˜s admission occurred after two, and sometimes more, auditions, in which the necessary number of choristers was selected. The requirements were many, but they were not too difficult for the children. The skills that the exam questionnaire was designed to assess were grouped into three equally important categories: musical abilities, vocal qualities, and performance emotionality. These were the three main points in Boncho Bochevâ€˜s artistic work.